Unique Post-telemetry Recapture Enables Development of Multi-Element Isoscapes From Barnacle Shell for Retracing Host Movement - Pearson, Ryan M.; van de Merwe, Jason P.; Gagan, Michael K.; Connolly, Rod M. (Frontiers in Marine Science, 2020)
Many ecological investigations rely on understanding the movement of animals through marine environments. Most available tracking techniques are invasive (e.g. tissue sampling) and require extensive effort and/or cost (e.g. capture-mark-recapture or satellite telemetry). The isotopic compositions of barnacle shells (δ13C and δ18O) are known to record the ambient water temperature and salinity conditions in which they grew. Thus, isotopic analysis of ‘hitchhiking’ barnacles on animals or objects has the potential to yield information about their movement between water bodies of varying isotopic properties. We present, for the first time, isotopic data for barnacle shell samples that grew on a satellite-tracked sea turtle host. The satellite telemetry record, together with documented barnacle growth rates, allowed for sequential samples from individual barnacle shells to be assigned a specific time and location for direct comparison of isotope values to environmental conditions. We developed models that allow barnacle shell δ13C and δ18O to be linked, with a high degree of predictability, to sea surface temperature (SST) and salinity (SSS). Our sea turtle case study demonstrated how these models can be used to create isoscapes, allowing hosts to be tracked in space and time at higher resolution than most attempts to use soft-tissue isotopes for a similar purpose, and at considerably lower cost than satellite telemetry. The conceptual advance presented here could be applied widely to understand the movement of any animal or object that carries hitchhiking barnacles.